Mesozoic Ostracoda from Portugal (Cabral Type Collection) - Cabral, Maria Cristina; Lord, Alan (Zootaxa, 2017)
This paper reports the deposition of a collection of type and figured material in the Senckenberg Museum, Frankfurt-am-Main. It has proved necessary to make certain taxonomic revisions that have come to light in recent years concerning the paper by Damotte, Cabral & Berthou (1990) on the Aptian of Portugal. Original names are cited below.